Designing peptide inhibitor of insulin receptor to induce diabetes mellitus type 2 in animal model Mus musculus. (October 2016) - Permatasari, Galuh W.; Utomo, Didik H.; Widodo,
Graphical abstract: Highlights: A novel design of peptide inhibitor competitive insulin receptor is proposed. The peptide inhibitor developed based on the binding site of insulin-IR. Modification of peptide performs to obtain the promising peptide inhibitor. The complex of modified peptide-IR is more stable than the commercially IR blocker. Abstract: A designing peptide as agent for inducing diabetes mellitus type 2 (T2DM) in an animal model is challenging. The computational approach provides a sophisticated tool to design a functional peptide that may block the insulin receptor activity. The peptide that able to inhibit the binding between insulin and insulin receptor is a warrant for inducing T2DM. Therefore, we designed a potential peptide inhibitor of insulin receptor as an agent to generate T2DM animal model by bioinformatics approach. The peptide has been developed based on the structure of insulin receptor binding site of insulin and then modified it to obtain the best properties of half life, hydrophobicity, antigenicity, and stability binding into insulin receptor. The results showed that the modified peptide has characteristics 100 h half-life, high-affinity −95.1 ± 20, and high stability 28.17 in complex with the insulin receptor. Moreover, the modified peptide has molecular weight 4420.8 g/Mol and has no antigenic regions. Based on the molecular dynamic simulation, the complex of modified peptide-insulin receptor is more stable than the commercial insulin receptor blocker. This study suggested that the modified peptide has the promising performance to block the insulin receptor activity that potentially induce diabetes mellitus type 2 in mice.